Digitalization, Market Trends, and Competitiveness in Enhancing MSME Sales Performance in Kupang, East Nusa Tenggara - Martina Kaisriani Rupa; Wizaldy Fabiano Hilnicputro; Fransiskus Marlon Reu (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
Micro, Small and Medium Enterprises (SMEs) play an important role in supporting regional economic growth, especially in developing areas. However, SMEs often face challenges in maintaining sales performance due to limited digital adoption, low competitiveness, and inability to follow market trends. Digitalization is considered an important strategy to improve competitiveness and expand market access in the modern business environment. This study aims to analyze the effect of competitiveness and market trends on MSME sales performance with MSME digitalization as a moderating variable in Kupang City, East Nusa Tenggara. This research uses a quantitative descriptive approach with a survey method. Data were collected through questionnaires distributed to MSME owners who have business identification numbers and have utilized digital media such as social media, e-commerce, or websites. The sampling technique used purposive sampling with 115 respondents selected from the MSME population. Data analysis was conducted using SPSS Statistics 24 through validity, reliability, and regression tests with moderation analysis. The results indicate that competitiveness and market trends significantly influence MSME sales performance, and digitalization strengthens the relationship between these variables. These findings highlight the importance of digital transformation in improving MSME sustainability and business performance in the digital era.